THU0578 ONLINE CME IMPROVES CLINICAL DECISION-MAKING IN THE MANAGEMENT OF PATIENTS WITH PSORIATIC DISEASE. (2nd June 2020) - Bell, E.; Gottlieb, A. B.; Mease, P. J.; Littman, G.; Via, M.
Abstract : Background: Psoriatic arthritis can be a challenging condition for rheumatologists to manage. Objectives: We assessed whether an online, virtual patient simulation (VPS) activity could improve the performance of rheumatologists in ordering appropriate tests, tailoring treatment options and selecting an evidence-based treatment for patients with PsA. Methods: This CME-certified VPS consisted of 2 patient cases presented in a platform that allowed physicians to assess the patients and complete open-field entries, choosing from an extensive database of diagnostic and treatment options reflecting the scope and depth of actual practice. After each decision, learners received clinical guidance (CG) based on current evidence and faculty recommendations. Clinical decisions were compared pre- and post-CG using a 2-tailed paired t-test to determine P values ( P <.05 is significant). Rationales for clinical decisions were collected in real time. Data were collected between 28 February 2019 and 16 May 2019 and reported here as % relative improvement, P value. Results: Case 1 (n=48 rheumatologists): 45 yr old female patient diagnosed with PSO 5 years ago. Current treatment with MTX 15mg & folic acid once weekly plus ibuprofen. Experiencing nausea and increasing skin lesions. Recently showing signs and symptoms of PsA. Statistically significant changes were observed for: Ordering appropriate tests to evaluate the patient (chemistry panel, 11%, P =.04; full blood count [FBC], 10%, P =.04; IFNƴ release assay for TB, 22%, P =.01; liver function tests [LFTs], 13%, P =.02; rheumatology consult, 19%, P =.01 and viral hepatitis panel, 52%, P <.001) Tailoring treatment options based on individual patient characteristics and available evidence (discontinue MTX [46%]and folic acid [140%], both P <.001; order patient education, 24%, P =.006; guidance on lifestyle changes, 20%, P =.01; preventative vaccines prior to ant-TNF therapy, 38%, P =.002 and a followup appointment at an appropriate timescale, 26%, P =.006) Selecting an evidence-based therapy for a patient newly diagnosed with PsA while on MTX therapy (adalimumab, 138%, P <.001) Case 2 (n=116 rheumatologists): 55 yr old male who has had PSO for 9 years. Developed joint symptoms 1 year ago. Diagnosed with PsA & treated with MTX/folic acid. Elevated liver enzymes noted after 9 months; treatment switched to adalimumab. Skin lesions much improved but ongoing issues with pain and stiffness in hands. Current medications are citalopram, adalimumab, simvastatin and triamcinolone for skin flares. Statistically significant changes were observed for: Ordering appropriate tests to evaluate the patient (C-reactive protein [9%], erythrocyte sedimentation rate [9%] and FBC [17%], all P<.01; Beck depression inventory [51%], BSAxPGA [21%], chemistry panel [15%], Global QoL 13%], Leeds enthesitis index [25%], LFTs [32%], PGA [21%], RAPID3 [63%], total BSA [137%]and X-ray of hands and feet [27%], all P <.001) Tailoring treatment options based on individual patient characteristics and available evidence (discontinue biologic DMARD [67%], order patient education [22%], physical therapy [31%] and occupational therapy 27%], preventative vaccines [35%], psychosocial counselling [31%] and a follow-up appointment at an appropriate timescale [32%], all P <.001) Selecting an evidence-based therapy for a patient with inadequate control of PsA on adalimumab (secukinumab, 152%, P <.001; ixekizumab, 167%, P =.01) Conclusion: These results demonstrate the success of immersive, online VPS education that engages physicians in a practical learning experience in improving their performance in managing patients with PsA. References: [1]https://www.medscape.org/viewarticle/902369 Disclosure of Interests: Elaine Bell: None declared, Alice B Gottlieb Grant/research support from:: Research grants, consultation fees, or speaker honoraria for lectures from: Pfizer, AbbVie, BMS, Lilly, MSD, Novartis, Roche, Sanofi, Sandoz, Nordic, Celltrion and UCB., Consultant of:: Research grants, consultation fees, or speaker honoraria for lectures from: Pfizer, AbbVie, BMS, Lilly, MSD, Novartis, Roche, Sanofi, Sandoz, Nordic, Celltrion and UCB., Speakers bureau:: Research grants, consultation fees, or speaker honoraria for lectures from: Pfizer, AbbVie, BMS, Lilly, MSD, Novartis, Roche, Sanofi, Sandoz, Nordic, Celltrion and UCB., Philip J Mease Grant/research support from: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Eli Lilly, Novartis, Pfizer, Sun Pharmaceutical, UCB – grant/research support, Consultant of: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Eli Lilly, Novartis, Pfizer, Sun Pharmaceutical, UCB – consultant, Speakers bureau: Abbott, Amgen, Biogen Idec, BMS, Eli Lilly, Genentech, Janssen, Pfizer, UCB – speakers bureau, Gwen Littman: None declared, Mark Via: None declared